The Sporothrix schenckii Gene Encoding for the Ribosomal Protein L6 Has Constitutive and Stable Expression and Works as an Endogenous Control in Gene Expression Analysis - Trujillo-Esquivel, Elías; Martínez-Álvarez, José A.; Clavijo-Giraldo, Diana M.; Hernández, Nahúm V.; Flores-Martínez, Alberto; Ponce-Noyola, Patricia; Mora-Montes, Héctor M. (Frontiers in Microbiology, 2017)
Sporothrix schenckii is one of the causative agents of sporotrichosis, a worldwide-distributed mycosis that affects humans and other mammals. The interest in basic and clinical features of this organism has significantly increased in the last years, yet little progress in molecular aspects have been reported. Gene expression analysis is a set of powerful tools that helps to assess the cell response to changes in the extracellular environment, the genetic networks controlling metabolic pathways, and the adaptation to different growth conditions. Most of the quantitative methodologies used nowadays require data normalization, and this is achieved measuring the expression of endogenous control genes. Housekeeping genes, whose expression is assumed to suffer minimal changes regardless the cell morphology, the stage of the cell cycle or the presence of harsh extracellular conditions are commonly used as controls in Northern blotting assays, microarrays, and semi-quantitative or quantitative RT-PCR. Since the biology of the organisms is usually species specific, it is difficult to find a reliable group of universal genes that can be used as controls for data normalization in experiments addressing the gene expression, regardless the taxonomic classification of the organism under study. Here, we compared the transcriptional stability of the genes encoding for elongation factor 1A, Tfc1, a protein involved in transcription initiation on Pol III promoters, ribosomal protein L6, histone H2A, β-actin, β-tubulin, glyceraldehyde 3-phosphate dehydrogenase, UAF30, the upstream activating factor 30, and the transcription initiation factor TFIID subunit 10, during the fungal growth in different culture media and cell morphologies. Our results indicated that only the gene encoding for the ribosomal protein L6 showed a stable and constant expression. Furthermore, it displayed not transcriptional changes when S. schenckii infected larvae of Galleria mellonella or interacted with immune cells. Therefore, this gene could be used as control for data normalization in expression assays. As a proof of concept, this gene was used to assess the expression of genes encoding for glycosidases involved in the protein N-linked glycosylation pathway, a histidine kinase whose expression is regulated during the fungal dimorphism, and a glycosidase that participates in sucrose assimilation.